EFEKTIVITAS KARANG TARUNA DALAM PEMBERDAYAAN SUMBER DAYA MANUSIA DI KELURAHAN BABAKAN KECAMATAN CIBEUREUM KOTA SUKABUMI - Khotimi Bahri (Jurnal Dialektika Politik, 2023)
Based on observations in the field, researchers are interested in this research because of several problems such as lack of youth participation in the Youth Organization, Lack of implementation of special activities in the field of Human Resources Empowerment by Youth Organization, Lack of effectiveness of Youth Organization empowerment for youth, Still low levels of youth awareness of Youth Organization. The theory used is Bastian's theory in Nawawi (2013). The purpose of this is to find out (1) Output (2) Policy (3) Procedures in the Effectiveness of Youth Organization in Empowering Human Resources in Babakan Village, Cibeureum District, Sukabumi City. The research method used is qualitative method. Key informants of this research are the Head of Kelurahan, Head of Youth Organization, Youth Organization Members, and Babakan Village Community, The number of informants is 6 people. And for determining the data sample used Purposive Sampling and Snowball Sampling. The data collection techniques used by literature study and field studies through observation and interviews. Data is collected using descriptive analysis techniques through the stages of data reduction, data presentation, the final stage is conclusion.  Karang Taruna is a social association as an organization or development group for each community that grows and develops on the basis of awareness and social responsibility from, by and for the community, especially the younger generation in the village / kelurahan area, especially those engaged in social welfare efforts. However, Karang Taruna in Babakan Village has not been achieved due to the lack of participation from the community which has an impact on Karang Taruna in empowering human resources. And until now the Babakan Village Youth Organization is still in the development stage, so that this organization can be sustainable towards better Human Resource Empowerment.